Kenyan, Christian, Queer : Religion, LGBT Activism, and Arts of Resistance in Africa - Van Klinken, A. S. (Book collections on Project MUSE., 2019)
"Examines the role of religion in LGBT activism in Kenya. Offers case studies of creative forms of queer visibility through which Kenyan LGBT individuals organize and present themselves in the public domain while critically engaging and appropriating Christian beliefs, symbols, and practices"--